What do Counsellors think they are doing? - Schneider, Brynah; Martin, Jack (Canadian Journal of Counselling and Psychotherapy, 2008)
Counsellors' identifications of seven commonly employed counsellor response modes were studied in order to enhance understanding of counselling from the phenomenological perspective of therapists. The method we used was developed by Vallacher and Wegner (1985, 1987) to study ways in which individuals identify actions in social contexts. Results were that counsellors tended to identify most of the response modes studies in a multifaceted manner that included high-level identities indicative of why a response mode is employed, as well as low-level identities concerned with how a response mode is executed. We interpreted our results to demonstrate that counsellors' theories of counselling actions are multifaceted, perhaps reflecting their initiation into the 'language game' or 'subculture' of counselling. Results were not affected by differences in counselling experience over a range of from 4 to 25 years of participation as a therapist in counselling.